Arte-educação nos contextos de periferias urbanas: um desafio social - Nascimento, Roseli Machado Lopes do (2010)
In the course of recent decades, the Supplementary Education or Non-Formal Education took important space in NGOs (Non Governental Organization) and in socio-educational works developed directly by the public power, with particular emphasis in the practices of Art-education, including many artistic languages aimed to occupy the opening intercalated public fundamental school activities. Such works happen, mainly, in the outskirts of urban centers, or even in the regions of slums in the center of the town. Most of this area is inhabited by a predominantly black population, migrant or a descendant of Northeast immigrants living in what Souza Martins would call contexts of perverse inclusion . It is in this scenario where Art-education takes place: a complex area of knowledge with many specificities, precisely because of its target audience and the geographical area where it develops. Art-education developed in the outskirt of urban area, what does it want? How does it act concerning issues dealing with perverse inclusion of this population, such as, racism, discrimination and the prejudice found in such places? In which way the art-educator deals with the issues related to cultural universe of this people (religious options, musical tastes and food, values, etc.) ? We´ve found, by observing the everyday spaces, where art-educational activities occur, as well as by the development of courses and workshops we offer about the theme, where a number of questions are involved in this actions and have impact on the performance of professionals in their daily. However, which critical benchmarks guide his action day to day? We must not forget that is in the Art that the human is recognized as a builder of self and that, despite the life and its hardships, the Art teaches to understand and develop alternatives for survival and the transformation of his reality